Poczet polskich krolowych, ksieznych i metres - Satala, Zbigniew (Szczecin : Glob, 1990)
Biographies of royal and noble Polish women across the centuries.
Includes bibliographical references (p. 271-[272]).
Keywords: Queens -- Poland -- Biography; Princesses -- Poland -- Biography